Robertsonian fusion triggers recombination suppression on sex chromosomes in Coleonyx geckos - Lisachov, Artem; Tishakova, Katerina; Romanenko, Svetlana; Lisachova, Lada; Davletshina, Guzel; Prokopov, Dmitry; Kratochvíl, Lukáš; O Brien, Patricia; Ferguson-Smith, Malcolm; Borodin, Pavel; Trifonov, Vladimir (Scientific reports, 2023)
The classical hypothesis proposes that the lack of recombination on sex chromosomes arises due to selection for linkage between a sex-determining locus and sexually antagonistic loci, primarily facilitated by inversions. However, cessation of recombination on sex chromosomes could be attributed also to neutral processes, connected with other chromosome rearrangements or can reflect sex-specific recombination patterns existing already before sex chromosome differentiation. Three Coleonyx gecko species share a complex X1X1X2X2/X1X2Y system of sex chromosomes evolved via a fusion of the Y chromosome with an autosome. We analyzed synaptonemal complexes and sequenced flow-sorted sex chromosomes to investigate the effect of chromosomal rearrangement on recombination and differentiation of these sex chromosomes. The gecko sex chromosomes evolved from syntenic regions that were also co-opted also for sex chromosomes in other reptiles. We showed that in male geckos, recombination is less prevalent in the proximal regions of chromosomes and is even further drastically reduced around the centromere of the neo-Y chromosome. We highlight that pre-existing recombination patterns and Robertsonian fusions can be responsible for the cessation of recombination on sex chromosomes and that such processes can be largely neutral.
Keywords: Animals; Y Chromosome; pohyb buněk; ještěři; Female; Cell Movement; mužské pohlaví; zvířata; pohlavní chromozomy; Male; Recombination, Genetic; rekombinace genetická; Sex Chromosomes; Lizards; chromozom Y; ženské pohlaví